2005
DOI: 10.1523/jneurosci.3355-05.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Dysfunction of the Cholesterol Biosynthetic Pathway in Huntington's Disease

Abstract: The expansion of a polyglutamine tract in the ubiquitously expressed huntingtin protein causes Huntington's disease (HD), a dominantly inherited neurodegenerative disease. We show that the activity of the cholesterol biosynthetic pathway is altered in HD. In particular, the transcription of key genes of the cholesterol biosynthetic pathway is severely affected in vivo in brain tissue from HD mice and in human postmortem striatal and cortical tissue; this molecular dysfunction is biologically relevant because c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
209
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(220 citation statements)
references
References 51 publications
11
209
0
Order By: Relevance
“…Previous studies reported that SREBP activity and its nuclear translocation were reduced in an inducible cell model of HD and in R6/2 brains. 7 Reduced nuclear levels of the N-terminal active fragment of SREBP2 (Nt-BP2) were also found in R6/2 astrocytes compared with wt astrocytes (Supplementary Figure 5a) and mRNA levels of SREBP2, but not of SREBP1, were decreased in HD NS-derived astrocytes compared with controls (Supplementary Figure 5b). Notably, a SRE sequence is present in the promoter region of SREBP2, 24 suggesting that reduced SREBP2 activation may in turn affect srebp2 gene expression.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies reported that SREBP activity and its nuclear translocation were reduced in an inducible cell model of HD and in R6/2 brains. 7 Reduced nuclear levels of the N-terminal active fragment of SREBP2 (Nt-BP2) were also found in R6/2 astrocytes compared with wt astrocytes (Supplementary Figure 5a) and mRNA levels of SREBP2, but not of SREBP1, were decreased in HD NS-derived astrocytes compared with controls (Supplementary Figure 5b). Notably, a SRE sequence is present in the promoter region of SREBP2, 24 suggesting that reduced SREBP2 activation may in turn affect srebp2 gene expression.…”
Section: Resultsmentioning
confidence: 91%
“…Similar results were obtained with four other independent differentiations. (j) Neurite outgrowth quantification in Q140/7 neurons under glial-free conditions (vehicle) or in the presence of increasing doses of cholesterol (3,5,7,10,12, and 20 μg/ml) immunostained for MAP2. The graph shows the mean (a.u.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations